A 2023 update on the performance of ionic-liquid proton-exchange-membrane fuel cells - East, Allan L. L.; Nguyen, Cuong M.; Hempelmann, Rolf (Frontiers in Energy Research, 2023)
A mini-review is provided of the literature concerning the performance of proton-exchange-membrane fuel cells (PEMFCs) containing (immobilized) ionic liquids as possible electrolytes, focusing on papers reporting performance metrics (power and current densities). For over a decade, and especially for combined heat and power applications, there has been a drive to design an ionic-liquid-holding membrane that could operate well under non-humidifying (water-free) conditions above 100°C. Such a goal has not yet been achieved: reported power densities are still below those of traditional low-temperature fuel cells. Other recent reviews have already pointed to three main issues: poor conductivity, poor cathode (oxygen-reduction) kinetics, and seepage of the liquid from the membrane. In this review, IL-PEMFCs are grouped into three IL classes (protic, aprotic, and polymerized), performance metric data are summarized, the cases producing the top ten peak power densities of the last 5 years are discussed, and the conductivity mechanisms of the leading cases are elucidated. Purely vehicular protic ILs appear to be too slow, and the trend toward enhanced Grotthuss H+ relays via polymerized ILs is revealed.